'What is wrong with a woman being chief?' Women Chiefs and Symbolic and Substantive Representation in Botswana. (April 2016) - Bauer, Gretchen
Across the globe women are accessing national legislatures and executives in unprecedented numbers. Over the last 25 years several African countries have led the way in women's representation in parliaments and, more recently, in cabinets. At the same time, governments and foreign donors are increasingly focusing on the role of traditional leaders in local-level politics as states democratize and decentralize across the continent. Once considered hopelessly undemocratic and patriarchal, traditional leaders are more recently viewed in many African countries as one half of a viable and effective hybrid system at the local level. In addition, whereas the role of chief has been largely the preserve of African men, African women are increasingly asserting a right to become chief. This article, using Botswana as a case study, suggests that the increased presence of women in national legislatures and executives may be having a symbolic representation effect on African women who are insisting that they too may access political power, even in positions formerly unavailable to them, such as chief. This article further suggests that, like their women counterparts in African parliaments, once they gain access to political office, women chiefs may substantively represent women's interests, in venues such as a House of Chiefs and in their communities.